2021
DOI: 10.3892/mco.2021.2423
|View full text |Cite
|
Sign up to set email alerts
|

Standard therapy‑resistant small cell lung cancer showing dynamic transition of neuroendocrine fate during the cancer trajectory: A case report

Abstract: While small cell lung cancer (SCLC) has been treated as a single disease historically, recent studies have suggested that SCLC can be classified into molecular subtypes based on the expression of lineage transcription factors such as achaete-scute homolog 1 (ASCL1), neurogenic differentiation factor 1 (NEUROD1), POU domain class 2 transcription factor 3 (POU2F3) and transcriptional coactivator YAP1 (YAP1). These transcription factor-based subtypes may be specifically targeted in therapy, and recent studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…NLR peaked before immunotherapy then rapidly declined, mirroring his tumor regression. Elevated NLR is associated with poor prognosis across cancer types ( 13 , 14 ). The sharp drop in NLR following immunotherapy corresponds with the patient’s exceptional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…NLR peaked before immunotherapy then rapidly declined, mirroring his tumor regression. Elevated NLR is associated with poor prognosis across cancer types ( 13 , 14 ). The sharp drop in NLR following immunotherapy corresponds with the patient’s exceptional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…TEM8/ANTXR1 upregulation has been described in a variety of solid tumors types including triple negative breast cancer (Xu et al, 2021), prostate cancer (Li et al, 2021a), gastric cancer (Li et al, 2021b;Sun et al, 2021), pancreatic cancer (Alcalá et al, 2019), angiosarcoma (Kusaba et al, 2021(Kusaba et al, ), colon cancer (Ł et al, 2021, and NSCLC (Gong et al, 2021). Lineage plasticity with a transformation from adenocarcinomas to carcinomas with neuroendocrine differentiation has been described in a variety of solid tumors, including lung and prostate primary tumors (Farrell et al, 2017;Rubin et al, 2020;Ito et al, 2021). This transformation is often associated with the development of therapy resistance and portends poor outcomes for patients.…”
Section: Seneca Valley Virus In Well Differentiated Neuroendocrine Tu...mentioning
confidence: 99%
“…Although the majority of SCLC do not respond to immunotherapy, alterations in NOTCH signalling may also influence tumour susceptibility to immunotherapy and allow for selection of patients who may respond 98,105 . Some studies have shown intratumoral heterogeneity of NOTCH signalling in mouse models, as well as shifts to increased NOTCH signalling and predominance of neuroendocrine marker‐low cell populations in cell lines exposed to chemotherapeutic agents, suggesting that the SCLC phenotype could also potentially be dynamically regulated within an individual tumour during therapy and require specific adjustments in patient management 96–98,100,106 . Further understanding of how the individual tumour phenotype evolves over the disease course could therefore be utilised to tailor therapy in patients with tumour persistence or recurrence.…”
Section: Molecular Characteristics Of High‐grade Neuroendocrine Carci...mentioning
confidence: 99%